Inhibitory Mechanism of Epsilon-poly-L-Lysine against Botrytis cinerea in Apples - Yong DOU; Jing DONG; Cheng CHEN; Peihong HU; Xinchi LIU; Lingwei KONG (Shipin gongye ke-ji)
The aim of the study was to investigate the inhibitory effect and mechanism of ε-poly-L-lysine on Botrytis cinerea causing gray mold in apples. The effects of different concentrations of ε-PL on colony diameter, spore germination, mycelial growth of B. cinerea, and its effect on controlling gray mold in apples were studied. The changes in cell permeability, antioxidant enzyme activities, cellular soluble protein and nucleic acid leakage, malonaldehyde content, and reactive oxygen species of B. cinerea were also investigated. The results showed that the minimum inhibitory concentration of ε-PL against B. cinerea was 400 mg/L, and the concentration of ε-PL could effectively control gray mold in apples. ε-PL concentration above 100 mg/L could significantly inhibit the spore germination and mycelium growth of B. cinerea (P<0.05), damage the spore membrane structure, and cause the leakage of soluble protein and nucleic acid, resulting in atrophic, small, and even dissolving spores. In addition, ε-PL concentration above 100 mg/L could significantly reduce the activities of superoxide dismutase, polyphenol oxidase, and catalase of B. cinerea and increase the content of malonaldehyde (P<0.05). In conclusion, ε-PL could damage the cell membrane structure of B. cinerea spores, increase cell permeability, and inhibit the activities of antioxidant enzymes, promote the accumulation of reactive oxygen species. This increased the degree of lipid peroxidation of the spore membrane, damaged the spore structure, and ultimately inhibited the growth of B. cinerea. This study laid a foundation for applying ε-PL in the prevention and control of postharvest diseases of apples and had high application value.